(untitled) (Trabalho & Educação, 2016)
The world of work has been transformed in recent decades, supported by new information and communication technologies and new forms of organizational management. Those changes resulted, among other effects, on the decrease of industrial workers, the increase in the services’ sector, the marked entry of women into the workforce and particularly in higher unemployment, precariousness of work and intensification of the journey of those who are employed. Some authors even question the centrality of labor. Supposing that labor is a source of meaning and valuation of personal and social life, we wonder how young people position themselves at those issues, even immersed in a world of uncertainty and fluidity. Therefore, the research aimed to identify and analyze the significance of work to 16 young students of both sexes, aged between 16 and 19 years, graduating from technical courses in Building, Electrical-Technic, Mechanics and Roads integrated with High School at the Federal Institute of Education, Science and Technology of Espírito Santo (IFES). Using a qualitative approach, taking semi-structured interviews as a tool, the testimony of these young students were analyzed by the method of interpretation of meanings, according to the construction of their careers and their life projects. The main topics presented and discussed were the following: life projects reported by the young students show an association between study and work, that is, young people have their day-to-day permeated by a school life aiming at the future entry into the labor; the aspiration of joining a university as a means to ascend to a valuable professional life, which requires effort and dedication to take a university entrance exam ; based on the new requirements of the labor market and taking their parents’ work as a reference, the meaning of labor is presented and questioned by the participants, either as a duty, or as human nature, sometimes as a means of wish fulfillment and personal achievement, the "free time" is not synonymous of leisure and rest, it is often used with learning activities to boost school’s obligations. Future is presented as a range of opportunities and a source of uncertainty. We observed that the work activity is the center of life and activities of these youths, as a way of preparing for a future career, anchoring other projects as the possibility of travel, realization and even survival. ___ O mundo do trabalho vem se transformando nas últimas décadas, apoiado em novas tecnologias de informação e comunicação e novas formas de gestão organizacional. Tais transformações resultaram, entre outros efeitos, na diminuição do operariado industrial, no aumento do setor de serviços, no ingresso acentuado de mulheres na força de trabalho e, principalmente, em maior desemprego, em precarização do trabalho e intensificação da jornada dos que se encontram empregados. Partindo do pressuposto de que o trabalho é fonte de significação e de valoração da vida pessoal e social, esta pesquisa teve por objetivo conhecer e analisar os significados do trabalho de 16 jovens estudantes, de ambos os sexos, com idades entre 16 e 19 anos, concluintes dos cursos do ensino médio integrado de um Instituto Federal de Educação, Ciência e Tecnologia. Utilizando abordagem qualitativa e tendo como instrumento entrevistas semiestruturadas, os depoimentos desses jovens estudantes foram analisados com base no método de interpretação de sentidos, de acordo com a construção de suas trajetórias e seus projetos de vida. As principais temáticas apresentadas e analisadas foram estas: projetos de vida relatados pelos jovens estudantes que apontam uma associação entre estudo e trabalho, ou seja, os jovens têm o seu cotidiano permeado pela vida escolar visando ao ingresso futuro no mundo do trabalho; a aspiração de ingressar na universidade como um meio de galgar uma vida profissional valorizada, o que requer esforço e dedicação por meio da realização do exame vestibular; o sentido do trabalho é apresentado e questionado pelos participantes, ora como dever e natureza humana, ora como via de realização pessoal e de desejos, baseando-se nas novas exigências do mercado de trabalho e tendo o trabalho dos pais como referência; o "tempo livre" não é sinônimo de lazer e descanso, sendo muitas vezes utilizado com atividades de aprendizagem para reforçar as obrigações escolares. O futuro apresenta-se como uma gama de oportunidades e como fonte de incertezas. Foi possível observar que a atividade de trabalho está no centro da vida e das atividades desses jovens, por meio da preparação para uma futura profissão, ancorando outros projetos como possibilidade de viagens, de realização e mesmo de sobrevivência.